Wpływ poziomu poczucia koherencji na podejmowanie aktywności prozdrowotnych w grupie studentów warszawskich uczelni wyższych = The impact of the sense of coherence to take pro-health activities in a group of students of Warsaw universities - Joanna Skonieczna; Elwira Smoleńska; Jolanta Makaruk; Dominik Olejniczak (Kazimierz Wielki University, 2015)
Skonieczna Joanna, Smoleńska Elwira, Makaruk Jolanta, Olejniczak Dominik. Wpływ poziomu poczucia koherencji na podejmowanie aktywności prozdrowotnych w grupie studentów warszawskich uczelni wyższych = The impact of the sense of coherence to take pro-health activities in a group of students of Warsaw universities. Journal of Education, Health and Sport. 2015;5(11):188-196. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33763 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A188-196 https://pbn.nauka.gov.pl/works/668907 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 10.11.2015.   Wpływ poziomu poczucia koherencji na podejmowanie aktywności prozdrowotnych w grupie studentów warszawskich uczelni wyższych   The impact of the sense of coherence to take pro-health activities in a group of students of Warsaw universities   Joanna Skonieczna (1), Elwira Smoleńska (2), Jolanta Makaruk (2), Dominik Olejniczak (1)   1. Zakład Zdrowia Publicznego, Warszawski Uniwersytet Medyczny, Szpital Banacha (Kampus Banacha), blok F, Banacha 1a, 02-097 Warszawa 2. Studenckie Koło Naukowe Zdrowia Publicznego, sekcja Promocji Zdrowia, Warszawski Uniwersytet Medyczny   Słowa kluczowe: poczucie koherencji, promocja zdrowia, student, zachowania zdrowotne.   Keywords: sense of coherence, health promotion, student health behaviors.     Streszczenie             Wstęp: Poczucie koherencji ma udowodniony naukowo wpływ na stan zdrowia człowieka. Istotne znaczenie ma wiek, w którym jednostka zaczyna stosować się do zasad zachowań prozdrowotnych. W młodszym wieku łatwiej nabyć prozdrowotne nawyki.             Cel: Ocena podejmowania wybranych zachowań prozdrowotnych, pomiar poziomu poczucia koherencji wśród warszawskich studentów i studentek oraz analiza wpływu poziomu poczucia koherencji na podejmowanie zachowań prozdrowotnych.             Materiał i metody: Badanie przeprowadzono przy użyciu autorskiego kwestionariusza składającego się z 16 pytań (metryczkowych oraz dotyczących podejmowania zachowań prozdrowotnych) oraz standaryzowanego Kwestionariusza Orientacji Życiowej SOC-29. Badaniem objęto 292 osoby studiujące w m.st. Warszawie, w tym 193 (66%) kobiety.             Wyniki: Przeprowadzone badanie wykazało, iż 53% kobiet w ogóle nie wykonuje badań cytologicznych, 34% kobiet nie wykonuje samobadania piersi, a 58% mężczyzn nie wykonuje samobadania jąder. 52% badanych zadeklarowało podejmowanie dodatkowej aktywności fizycznej co najmniej raz w tygodniu. Blisko 98% osób wskazało, iż myje ręce po wyjściu z toalety. Studenci najczęściej określają swój stan zdrowia jako bardzo dobry (37%) lub dobry (35%). Średnie ogólne poczucie koherencji wyniosło 125,48 pkt. Poczucie koherencji jest skorelowane z samooceną stanu zdrowia studentów, regularnym spożywaniem śniadań i podejmowaniem aktywności fizycznej.             Wnioski: Poczucie koherencji można modyfikować i wpływać na jego wzrost. Wysokie SOC pozytywnie wpływa na podejmowanie niektórych zachowań prozdrowotnych. Należy podjąć działania mające na celu zwiększanie poczucia koherencji wśród młodych osób oraz badania naukowe w tym zakresie.     Abstract             Introduction: Sense of coherence has scientifically proven impact on human health.  The age at which individual begins take pro-health activities is very important. In an earlier age it easier to acquire health-promoting habits.             Aim: Evaluation of pro-health activities chosen by participants and measurement the level of coherence among Warsaw students.             Material and Methods: The study was conducted by authorial questionnaire which consisted of 16 questions. Additionally there was used Life Orientation Questionnaire SOC-29. Totally in the study took part 292 students from Warsaw, including 193 (66%) women.             Results: The study showed that 53% of women in general do not make Pap tests, 34% of them do not make breast self-examination and 58% of men do not perform testicular self-examination. Around 52% of respondents declared undertaking any physical activity at least once a week. Nearly 98% of participants declared that they wash their hands after using the restroom. Students frequently describe their health as very good (37%) or good (35%). Average total sense of coherence amounted to 125.48 points. Sense of coherence is correlated with self-esteem health of students, regular breakfast eating and physical activity.             Conclusions: Sense of coherence can affect the growth of health. High SOC has a possitive impact on some health behaviors. Actions should be taken to increase the sense of coherence among young people therefore scientific research in this area are needed.